A novel CLCN5 pathogenic mutation supports Dent disease with normal endosomal acidification. Issue 8 (4th June 2018) - Bignon, Yohan; Alekov, Alexi; Frachon, Nadia; Lahuna, Olivier; Jean‐Baptiste Doh‐Egueli, Carine; Deschênes, Georges; Vargas‐Poussou, Rosa; Lourdel, Stéphane
Abstract: Dent disease is an X‐linked recessive renal tubular disorder characterized by low‐molecular‐weight proteinuria, hypercalciuria, nephrolithiasis, nephrocalcinosis, and progressive renal failure. Inactivating mutations of CLCN5, the gene encoding the 2Cl − /H + exchanger ClC‐5, have been reported in patients with Dent disease 1. In vivo studies in mice harboring an artificial mutation in the "gating glutamate" of ClC‐5 (c.632A > C, p.Glu211Ala) and mathematical modeling suggest that endosomal chloride concentration could be an important parameter in endocytosis, rather than acidification as earlier hypothesized. Here, we described a novel pathogenic mutation affecting the "gating glutamate" of ClC‐5 (c.632A>G, p.Glu211Gly) and investigated its molecular consequences. In HEK293T cells, the p.Glu211Gly ClC‐5 mutant displayed unaltered N‐glycosylation and normal plasma membrane and early endosomes localizations. In Xenopus laevis oocytes and HEK293T cells, we found that contrasting with wild‐type ClC‐5, the mutation abolished the outward rectification, the sensitivity to extracellular H + and converted ClC‐5 into a Cl − channel. Investigation of endosomal acidification in HEK293T cells using the pH‐sensitive pHluorin2 probe showed that the luminal pH of cells expressing a wild‐type or p.Glu211Gly ClC‐5 was not significantly different. Our study further confirms that impaired acidification of endosomes is not the only parameter leading to defective endocytosis in Dent disease 1. Abstract : Dent disease type 1, a renal tubular disorder characterized by low‐molecular‐weight proteinuria, hypercalciuria, nephrocalcinosis, and progressive renal failure is associated with mutations in the gene encoding the 2Cl − /H + exchanger ClC‐5. This transporter plays a crucial role in receptor‐mediated endocytosis by permitting acidification of the early endosomes of the proximal tubule. We have demonstrated that a novel mutation affecting the "gating glutamate" converts ClC‐5 into a Cl − channel without impairing acidification of endosomes.